2021
DOI: 10.3390/microorganisms9102098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Pathogenic Free-Living Amoeba from Household Biofilm Samples in Iran: A Risk Factor for Acanthamoeba Keratitis

Abstract: Free-living amoeba (FLA) are ubiquitously distributed in the environment. However, they are also the causative agents of opportunistic infections in humans and other animals. A biofilm comprises any syntrophic consortium of microorganisms in which cells stick to each other and often also to a surface. Moreover, FLA have been detected in various biofilms around the world. Therefore, the present study aimed to check for presence of FLA in samples from household biofilms in Iran and to characterize them at the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Recent study has reported that Vermamoeba (Hartmannella) vermiformis as the etiological agent of an infection close to the eye of a female patient [5]. Some investigators checked localization of FLAs in our environments because they thought that FLA is a potential pathogen or vector of bacterial pathogens [33][34][35][36]. FLAs were detected with potential human pathogenic bacteria in stored water in rural households in South Africa [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has reported that Vermamoeba (Hartmannella) vermiformis as the etiological agent of an infection close to the eye of a female patient [5]. Some investigators checked localization of FLAs in our environments because they thought that FLA is a potential pathogen or vector of bacterial pathogens [33][34][35][36]. FLAs were detected with potential human pathogenic bacteria in stored water in rural households in South Africa [34].…”
Section: Discussionmentioning
confidence: 99%
“…Beside the classification according to cyst size and shape (group I–III) (Marciano-Cabral and Cabral 2003 ), Acanthamoeba spp. based on the SSU rDNA can be divided into 23 genotypes (T1–T23) (Norouzi et al 2021 ); however, most of the AK cases are caused by the T4 genotype (Jercic et al 2019 ). In this study, an Acanthamoeba sp.…”
Section: Resultsmentioning
confidence: 99%
“…The ameba trophozoites remained in an irregular shape because of their undisrupted acanthopodia, flattened onto the contact lens, and coated with bacteria. Biofilms produced by microorganisms have been shown to help protect ameba [ 39 ]. The biofilms produced by S. aureus and P. aeruginosa may protect Acanthamoeba from the cytotoxic effect of P. betle leaf extract, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%